DIRECTIONS OF FUNCTIONAL FOOD MARKET DEVELOPMENT IN LIGHT OF NEW CONSUMER TRENDS - Szwacka-Mokrzycka, Joanna; Kociszewski, Michał (Acta Scientiarum Polonorum. Oeconomia, 2019)
The main aim of the article is to present the directions of functional food market development in Poland and in the world against the background of changing patterns of consumer behaviour. The presentation of the concept and functions performed by this product category shall be the starting point. Consumer trends developed over the last decade are presented, with particular attention paid to changes in food consumer preferences and the role of marketing activities in this process. The last part of the study refers to the trends in the development of functional food in Poland compared to the world market.